2000
DOI: 10.1103/physrevd.62.104012
|View full text |Cite
|
Sign up to set email alerts
|

Supermassive boson star at the galactic center?

Abstract: We explore whether supermassive nonbaryonic stars ͑in particular boson, miniboson, and nontopological soliton stars͒ might be at the center of some galaxies, with special attention to the Milky Way. We analyze, from a dynamical point of view, what current observational data show, concluding that they are compatible with a single supermassive object without requiring it to be a black hole. Particularly, we show that scalar stars fit very well into these dynamical requirements. The parameters of different models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
177
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(180 citation statements)
references
References 64 publications
3
177
0
Order By: Relevance
“…In Figure 2 we show the variation of the rotation curve when the value of M changes. It is evident that this would affect only the kinematics in the central parts of the galaxy, exactly in the same way as the mass of the central object should do [21]. In Fig.…”
Section: Dark Matter In Galaxiesmentioning
confidence: 83%
“…In Figure 2 we show the variation of the rotation curve when the value of M changes. It is evident that this would affect only the kinematics in the central parts of the galaxy, exactly in the same way as the mass of the central object should do [21]. In Fig.…”
Section: Dark Matter In Galaxiesmentioning
confidence: 83%
“…The integration of the Klein-Gordon equation (5)(6)(7)(8) and the BSSN variables is performed using the method of lines with second order centered differencing in space. For the time integration a third order Runge-Kutta (RK3) algorithm is used [20].…”
Section: A Evolution In Timementioning
confidence: 99%
“…Recently Boson Stars have appeared in many contexts. Traditionally they were proposed to be alternatives of compact objects [1,3]; they have been proposed as candidates for dark matter [4]; this includes the possibility to emulate galactic supermassive Black Holes [5]; they have even been considered as sources of gravitational waves [6]; and they have been used in the field of numerical relativity to test evolution formulations of Einstein's equations and experience with gauge conditions [7], since these objects are very tractable in the sense that they have no defined surface and their dynamics do not tend to form shocks, and therefore sophisticated techniques -like shock capturing methods-are not required. Moreover, BSs define sequences of equilibrium configurations which serve to test a numerical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…After charting the kinematics of stars swirling around the central regions of the Milky Way [118] [119] [120], it has been found that the total mass of the region enclosed within a radius of 2 × 10 15 cm is approximately 3.7 × 10 6 M ⊙ , far more compact than what is possible for a stable distribution of individual objects; total gravitational collapse is required, according to GR. Indeed, the only remaining alternative candidate, other than a black hole, to describe the behavior of the innermost stellar orbits in the center of the Milky Way Galaxy comes from particle physics, and is known as a boson star [121]. Mass estimates for central supermassive black holes in about twenty nearby galaxies are also available (see review in [122]).…”
Section: Active Galactic Nucleimentioning
confidence: 99%